Maqāṣid al-Sharī‘a as the Foundation of Islamic Moderation: Theo-Philosophical Insight against Extreme Religious Ideology - Mutawali Mutawali (Ulumuna, 2023)
The emergence of neo-Khawarij groups in the contemporary world has attracted domestic and international attention. These groups have shown a propensity for growth, as evidenced by the increasing number of terrorist attacks in the form of suicide bombings carried out in the name of Islam. Such acts of terror have led to Islam being labeled as a religion of hate, bigotry, and terrorism. Through the analysis of Maqāṣid al-sharī‘a in understanding Islamic texts, in this study, Islamic Moderation is proposed as a paradigm to reduce the penetration of radical ideology in religion. This study proposes the adoption of moderate Islam as a paradigm for countering the spread of radical ideologies within the religion. To this end, this paper begins with an overview of the references used by radical groups and the acts of terror they have committed. It then advocates for the importance of Maqāṣid al-sharī‘a in understanding Islamic texts. It offers the concept of moderate Islam as a precautionary measure for mitigating the penetration of radical ideologies.